The Improvement of Semen Quality by Dietary Fiber Intake Is Positively Related With Gut Microbiota and SCFA in a Boar Model - Lin, Yan; Wang, Ke; Che, Lianqiang; Fang, Zhengfeng; Xu, Shengyu; Feng, Bin; Zhuo, Yong; Li, Jian; Wu, Caimei; Zhang, Junjie; Xiong, Haoyu; Yu, Chenglong; et al. (Frontiers in Microbiology, 2022)
Although fiber-rich diets have been positively associated with sperm quality, there have not been any studies that have examined the effects of dietary fiber and its metabolites on sperm quality in young or pre-pubescent animals. In this study, we aimed to explore the effect of dietary fiber supplementation on semen quality and the underlying mechanisms in a boar model. Sixty purebred Yorkshire weaning boars were randomly divided into the four groups (T1–T4). Groups T1, T2, and T3 boars were fed diets with different levels of fiber until reaching 160 days of age and were then fed the same diet, while group T4 boars were fed a basal diet supplemented with butyrate and probiotics. Compared with T1 boars, sperm motility and effective sperm number were significantly higher among T3 boars. Meanwhile, at 240 days of age, the acetic acid and total short-chain fatty acid (SCFA) contents in the sera of T3 and T4 boars were significantly higher than those in T1 boars. The abundance of microbiota in T2 and T3 boars was significantly higher than that in T1 boars (P < 0.01). Moreover, dietary fiber supplementation increased “beneficial gut microbes” such as UCG-005, Rumenococcus, Rikenellaceae_RC9_gut_group and Lactobacillus and decreased the relative abundance of “harmful microbes” such as Clostridium_sensu_stricto_1, Romboutsia and Turicibacter. Collectively, the findings of this study indicate that dietary fiber supplementation improves gut microbiota and promotes SCFA production, thereby enhancing spermatogenesis and semen quality. Moreover, the effects of dietary fiber are superior to those of derived metabolites.